Penerapan Teknik Cognitive Restructuring dalam Layanan Bimbingan Karir untuk Meningkatkan Perencanaan Karir Siswa - Nurul Haerani (Universitas Mathla'ul Anwar Banten, 2026)
Immaturity in students' career planning is often not caused by a lack of information, but rather by mental barriers in the form of irrational thought patterns and cognitive distortions. This study aims to map the overview of previous career guidance implementations, identify the methods used, and analyze the opportunities and relevance of Cognitive Restructuring techniques as an alternative approach to improving the effectiveness of career guidance services. The method used in this study was library research by analyzing literature from accredited national journals from 2020-2025. The results of the study indicate that although various career guidance methods such as classical guidance, the use of digital technology media, and problem-solving techniques have proven effective in improving professional insight and student motivation, there are gaps where students' internal cognitive aspects have not been deeply touched. The research findings confirm that Cognitive Restructuring techniques through Doyle's seven-step procedure have very strong relevance in filling this gap. This technique has a great potential to help students identify, challenge, and replace irrational career-related thoughts with more rational, adaptive, and realistic mindsets. The conclusions of this study emphasize the importance of integrating a cognitive approach into career guidance services to ensure students not only have sufficient career information but also the mental maturity to make future decisions.